Adolescent male volleyballers' serve proficiency in Estonian championships in 2005, 2006 and 2008 - Stamm, M.; Stamm, R.; Koskel, S. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The study analyses volleyballers` performance at Estonian championships for Class C (up to 16-year-olds) in three tournaments - Tartu 2005, Viljandi 2006 and Rakvere 2008. The participants were members of the eight best teams of Estonia at the moment. Methods: To record the games an original computer program Game (Nõlvak, 1995) was used, which was first presented by R. Nõlvak (Stamm) in 1995 and has been introduced in the International Journal of Volleyball Research (Stamm et al, 2000). For simultaneous recording of the performance of two opposing teams, two computers equipped with the program Game were used. Parallel recordings were made by volleyball experts - Meelis Stamm and Raini Stamm. Twenty-eight indicators of proficiency in the game were registered, but in this study we focus only on the element of serve. Results: From our results we can conclude that in 2005 there were 278 serves which earned a point at once (aces) in 2006 - 204 serves, and in 2008 - 309 serves. When we look at the mistakes during the serves, we can see that in 2005 there were 308, in 2006 were 197 and in 2008 were 246 mistakes during the serve. From these numbers we can summarize, that boys serving quality is increasing. The same thing is when we look the proficiency of serve during the different years. It has been changing from 0,38 to 0,45. As long as it is not a longitudinal study but cross sectional, then we can`t say that the boys were getting better but we can say that the quality of coaching was improved. Discussion: The serve is playing more important role in the game from year to year. The meaning of serve has been changed. It has become a real attacking element and it is not any more simply the element for beginning the ball rally.